Infection factors related to nursing procedures in Intensive Care Units: a scoping review - Paiva,Renilly de Melo (2021)
ABSTRACT Objectives: to identify and map the invasive procedures performed by nursing that can cause Healthcare-Associated Infections in patients in Intensive Care Units. Methods: this is a scoping review carried out in the first half of 2018, based on search for studies in national and international databases, in which 2,209 studies were found, of which 35 constituted the final sample. The data were analyzed and organized by simple descriptive statistics. Results: among the invasive procedures performed by nursing that provide Healthcare-Associated Infections, delayed bladder catheter was indicated in 34 (66.67%) studies, the nasogastric catheter in 10 (19.61%) and the nasoenteral catheter in two (03.92%). Conclusions: in the face of such problems, better nursing planning and guidance for care in these invasive techniques becomes relevant and thus minimizes the incidence of infections.